Poly(m-phenylene isophthalamide)-reinforced polyethylene oxide composite electrolyte with high mechanical strength and thermostability for all-solid-state lithium metal batteries - Liu, Ya-Ning; Xiao, Zhen; Zhang, Wen-Kui; Zhang, Jun; Huang, Hui; Gan, Yong-Ping; He, Xin-Ping; Kumar, G. Gnana; Xia, Yang (Rare metals, 2022)
Polyethylene oxide (PEO)-based solid polymer electrolytes (SPEs) with flexibility, easy processability, low cost and especially strong ability to dissolve lithium salts have been regarded as promising alternatives to traditional flammable liquid electrolytes in next-generation high-safety and high-energy-density lithium metal batteries. However, the inferior mechanical strength and thermostability of PEO-based SPEs will raise the lithium dendritic penetration issue, further leading to the short circuit in batteries. In this work, aiming at enhancing the interfacial stability against Li dendrites of PEO-based SPEs, poly(m-phenylene isophthalamide) (PMIA) is introduced as a reinforcing phase for the rational design of PEO/PMIA composite electrolyte. Impressively, PMIA chain with meta-type benzene-amide linkages significantly improves the mechanical strength (1.60 MPa), thermal stability (260 °C) and ability to inhibit the growth of lithium dendrites (> 300 h at 0.1 mA·cm −2 ) of SPEs. Meanwhile, all-solid-state LiFePO 4 ||PEO/PMIA||Li cell demonstrates superior electrochemical performance in terms of high specific capacity (159.1 mAh·g −1 ), remarkable capacity retention (82.2% after 200 cycles at 0.5C) and excellent safety characteristics. No burning or explosion occurs under pressing, bending and cutting conditions. This work opens a new door in developing high-performance PEO-based electrolytes for advanced all-solid-state lithium metal batteries. Graphical abstract